Seismic response mitigation of structures with a friction pendulum inerter system. (15th August 2019) - Zhao, Zhipeng; Zhang, Ruifu; Jiang, Yiyao; Pan, Chao
Highlights: A friction pendulum inerter system (FPIS) is proposed to reduce seismic response. The FPIS uses an inerter without adding significantly more mass to the system. The impact of the FPIS's mechanical layout on response mitigation is investigated. An optimal design method is developed to meet the target structural performance. FPIS shows the robustness and outperforms FPS-TMD at response mitigation. Abstract: Introducing a tuned mass damper (TMD) into the friction pendulum system (FPS) has been proven to be an effective approach for improving the seismic performances of base-isolated structures. However, its seismic response mitigation effect is related to the quality of the mass employed, which unavoidably requires a necessary large mass under the requirement of a high seismic performance level. To avoid introducing the extra mass of the tuned mass damper (TMD) in the friction pendulum system (FPS) of a base-isolated structure, we herein introduce a lightweight inerter subsystem that has a series-parallel layout; comprises an inerter, a spring, and a damping element; and adds almost no mass. A structure isolated by the proposed friction pendulum inerter system (FPIS) was studied by nonlinear stochastic response analysis within a probabilistic framework, and an optimal design method for a structure with the FPIS was developed to simultaneously reduce the base shear force and the base isolation floor displacement. Based on the stochastic analysis results, parametric studies and a robustness analysis were conducted, and the impact of the FPIS's mechanical layout on the seismic response mitigation effect was investigated. The analysis results demonstrated that the FPIS significantly reduced structural responses under different types of seismic excitations. Using the proposed optimal design method, target base shear force can be achieved at a minimized cost to the base isolation floor displacement. Compared to the FPS system with a TMD, the proposed FPIS enhances the seismic response mitigation effect by avoiding the extra mass that increases the seismic energy input to the base isolation floor.